Latvijas cukura diabēta pacientu reģistra datu analīze - Al-Bacha, Mukhtar (Latvijas Universitāte, 2016)
Background Diabetes mellitus, a chronic disease with a worldwide burden, requiring a prolonged and complex manner of management, both for the condition and for its following complications. It is projected that in 2030 to be the 7th leading cause of death. Purpose of research Analysis and evaluation of different parameters of diabetes mellitus of the Latvian diabetes registry of 2013 and comparison with Swedish diabetes registry, and aim for improvement. Method used Statistics were used to describe different values in the form of diagrams and tables. Numerical calculations and software were used to produce the results in the study. Microsoft Excel 2013 was the main program in use for analyzing the registry data. Findings/results Diabetes type 2 is the most common type in Latvia. Around 2/3 of diabetic patients are females. 53% of diabetic females and 44% of diabetic males are obese. 56% of the diabetic patients have an HBA1c above the normal value. The commonest medication used to treat diabetes type 2 in Latvia is Metformin( Biguanides). Nearly 50 % of diabetic patients are obese. A high HBA1c value was seen in the obese group. A low HBA1c value was seen in the overweight group. 40 % of hypertensive patients have not reach their therapeutic goal. Cardiovascular diseases are the most common diagnosed complication, with a percentage of 24 % diagnosed patients. Mean HBA1c decreases with aging, in contrast to mean BMI that increases with aging. Changes of prescribes medications occurs when the HBA1c gets higher. Short- and long acting insulin are the second most used medications after metformin when HBA1c is >9%. Conclusion •Progression of type 2 diabetes among the Latvian population. •Increased complications, commonly, cardiovascular diseases, more care should be placed in this group of patients •Lifestyle modifications should be started and new diabetic educational programs should be introduced for a healthier life.
Analysis of the data from the Latvian Diabetes registry
Keywords: Medicīna; Latvijas cukura diabēta pacientu reģistra datu salīdzinošā analīze; Zviedru diabēts reģistra; cukura diabēts; tuklums, diabēta zāles